The historic town of Sandomierz as a tourist destination - Faracik , Robert (Turyzm/Tourism, 2017)
Towns are tourist destinations because of their material heritage, cultural events as well as a wide range of other attractions. A special role in contemporary tourism development is played by historic towns that offer tourists not only heritage but also combine their genius loci with contemporary human needs. Sandomierz is one of the oldest Polish towns with its origins going back to the early Piast period. The thousand years of its history is visible in a well-preserved urban-architectural complex which has successfully survived both world wars in the 20th c. Today's image of ‘tourist’ Sandomierz is connected with the TV serial of Ojciec Mateusz. The story, set in Sandomierz, has become a tourist attraction as well as an important means of promotion and creating an image of the town as a pleasant and hospitable place. The role of the serial as a factor for tourism development in terms of tourism infrastructure and volume of tourists dates from 2008. Sandomierz offers much else that has created favourable conditions for the development of new forms of tourism.